Lead-free piezoelectric ceramics based on (1 − x)BNKLLT–xBCTZ binary solid solutions synthesized by the solid-state combustion technique - Kornphom, Chittakorn; Vittayakorn, Naratip; Bongkarn, Theerachai (My University, 2016)
The aim of this work is to improve the electrical properties of BNKLLT ceramics with the addition of BCTZ. New binary (1 − x)BNKLLT-xBCTZ lead-free piezoelectric ceramics with different x contents between 0 and 0.10 (step 0.02) were fabricated by the solid-state combustion technique, where glycine was used as a fuel. The influences of x concentration on the phase evolution, morphology, and electrical behavior were investigated. The phase formation exhibited a coexistence of rhombohedral and tetragonal phases in all samples. With the increasing x content, the phase formation was dominated by a higher tetragonality. The average gain size continuously reduced from 1.52 to 0.96 µm when x content was increased. The maximum dielectric temperature (TSA) of these ceramics decreased with the increasing x content. The ferroelectric properties were further weakened with the increasing x content. The MPB region was obtained at x content of around 0.04 producing this sample and showed the highest dielectric constants (εr = 2720 and εSA = 6110) and an excellent piezoelectric constant (d33 = 295 pC/N).